1988
DOI: 10.1161/01.cir.78.2.302
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic heart disease mortality in Hispanics, American Indians, and non-Hispanic whites in New Mexico, 1958-1982.

Abstract: To describe trends in mortality from ischemic heart disease in New Mexico's Hispanic, American Indian, and non-Hispanic white populations, we used vital records data collected from 1958 through 1982. We calculated age-adjusted and age-specific mortality rates for ischemic heart disease for each of the state's principal ethnic groups. Death certificate data were used in combination with population estimates based on the censuses of 1960, 1970, and 1980. Age-adjusted mortality rates for ischemic heart disease am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
1

Year Published

1991
1991
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(21 citation statements)
references
References 42 publications
0
20
1
Order By: Relevance
“…Although similar observations about the rates of death from cardiovascular disease have been made in prior studies, 6 recent analyses suggest this may have been due to under-ascertainment of deaths in Hispanics 7 or failure to correct for confounding factors. 8 This, however, does not discount the possibility that the prevalence of cardiovascular disease is lower in Hispanics.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Although similar observations about the rates of death from cardiovascular disease have been made in prior studies, 6 recent analyses suggest this may have been due to under-ascertainment of deaths in Hispanics 7 or failure to correct for confounding factors. 8 This, however, does not discount the possibility that the prevalence of cardiovascular disease is lower in Hispanics.…”
Section: Discussionmentioning
confidence: 52%
“…6 However, more recent reports have argued that this could be explained by under-ascertainment of deaths 7 and that when adjusted for confounders, the rates of deaths were likely equal or in certain subgroups potentially higher. 8 This does not exclude, however, the possibility that the incidence or prevalence of cardiovascular disease in Hispanics is lower.…”
Section: Introductionmentioning
confidence: 99%
“…41 CVD is the leading cause of death among Hispanic males (28%) and females (34%). 41 Although earlier studies suggested that the age-adjusted mortality rates for major CVD among Mexican-Americans (28.8 and 26.6 per 100 000 men and women, respectively) were lower than those of AfricanAmericans (40.5 and 39.6, respectively) and whites (30.0 and 23.8 per 100 000), 42 recent data from the Corpus Christi Heart Project, reported a greater incidence of myocardial infarction (MI) in Mexican-Americans compared with non-Hispanic whites. 43 The age-adjusted MI incidence was higher by 1.25 and 1.52 among Mexican-American men and women compared with non-Hispanic whites, 44 with greater MI casefatality rate among Mexican-Americans than non-Hispanic whites.…”
Section: Hispanicsmentioning
confidence: 97%
“…N umerous studies over the past several decades, using vital statistics data, have demonstrated reduced rates of total and cardiovascular mortality in Hispanics (1)(2)(3)(4). Interestingly, epidemiological studies of cardiovascular risk factors have suggested that Hispanics are frequently more obese and insulin resistant compared with non-Hispanic whites (NHWs) and often, as a result, have higher triglyceride levels and lower HDL cholesterol levels (5)(6)(7)(8)(9)(10)(11)(12)(13).…”
mentioning
confidence: 99%